Pengaruh Solid Decanter dan Kompos Tandan Kosong Kelapa Sawit Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Pembibitan Utama: Program Studi Agroekoteknologi Fakultas Pertanian Universitas Andalas, Kampus 3 Unand Dharmasraya - Sari, Anisma; Rezki, Dewi (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2024)
This research regarding the effect of solid decanter and oil palm bunch compost on the growth of oil palm seedlings in the main nursery has been carried out at the Dharmasraya UNAND campus 3 experimental garden, from November 2019 to May 2020. The research objective was to obtain interactions between solid decanter and oil palm bunch compost and getting the best dose of solid decanter and oil palm bunch compost for the growth of oil palm seedlings in the main nursery. This study used a factorial completely randomized design (CRD) consisting of two factors with four treatment levels. The first factor is solid decanter (0 g/polybag, 300 g/polybag, 600 g/polybag, and 900 g/polybag) and the second factor is oil palm bunch compost (0 g/polybag, 750 g/polybag, 1500 g/polybag, and 2250 g/poly bag). The variables observed were plant height, stem diameter, number of leaves, leaf length, and leaf width. The results showed that there was an interaction between solid decanter and oil palm bunch compost on plant height, stem diameter, leaf length and leaf width. The treatment dose of 300 g/polybag solid decanter and 750 g/polybag of palm oil bunch compost showed the best growth in each variable.